2005
DOI: 10.4269/ajtmh.2005.73.276
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a New Microculture Method for Diagnosis of Visceral Leishmaniasis by Using Bone Marrow and Peripheral Blood

Abstract: We have demonstrated that the microculture method (MCM) enables the diagnosis of visceral leishmaniasis (VL) with samples from both the bone marrow (BM) and peripheral blood (PB). The MCM is superior to the traditional culture method (TCM) as determined by its higher sensitivity in the detection of promastigotes and the more rapid time for emergence of promastigotes. The sensitivity of MCM (100% in BMs and 77.8-100% in PB) was considerably higher than that of the TCM (37.5-100% in BMs and 0-100% in PB) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
(46 reference statements)
0
20
0
1
Order By: Relevance
“…In our previous studies, it has been shown that MCM is more sensitive than the other classical culture approaches in the diagnosis of visceral and cutaneous leishmaniasis. [25][26][27] It is already known that Leishmania parasites have developed a survival mechanism in which they stay viable in phagolysosome after infecting macrophages by receptor-based phagocytosis. 11 In the literature, it has been shown that parasites infect not only professional phagocytotic cells such as macrophages but also amnion epithelial cells, fibroblasts, kidney cells, and dendritic cells in mammalian hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, it has been shown that MCM is more sensitive than the other classical culture approaches in the diagnosis of visceral and cutaneous leishmaniasis. [25][26][27] It is already known that Leishmania parasites have developed a survival mechanism in which they stay viable in phagolysosome after infecting macrophages by receptor-based phagocytosis. 11 In the literature, it has been shown that parasites infect not only professional phagocytotic cells such as macrophages but also amnion epithelial cells, fibroblasts, kidney cells, and dendritic cells in mammalian hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Microcapillary culture was prepared every 7 days from ADMSCs culture infected by Leishmania parasites. [25][26][27] Detected motile promastigotes were counted and evaluated according to the method of Chulay and Bryceson 24 with slight modifications: Grade 0 = 0 parasites/all fields; Grade 1+ = 1-5 parasites/all fields; Grade 2+ = 6-10 parasites/all fields; Grade 3+ = 11-25 parasites/all fields; Grade 4+ = 26-50 parasites/all fields; Grade 5+ = 51-100 parasites/all fields; Grade 6+ > 100 parasites/all fields.…”
mentioning
confidence: 99%
“…Adaptation of this method to the microculture scale using microplates [7] can also be tested in order to facilitate the visualization of parasites during isolation period. Also, to investigate asymptomatic L. i. chagasi infection, PB can be used for culture isolation, since BM aspiration is only recommended for symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of macrophages in peripheral blood (PB) makes culture isolation suitable, as showed for children and adult patients infected with L. infantum from Mediterranean basin [7][8][9]. Most prominent L. infantum culture isolation techniques from PB presenting high sensitivity depends on sample washing with culture medium and concentration, or isolation of peripheral blood mononuclear cells (PBMC) [7,9], which are hard to be performed in laboratory routine, principally due to contamination risk during sample manipulation. Low efficiency of L. infantum isolation methods are probably related to immune complexes mediated parasite lysis [10,9].…”
mentioning
confidence: 99%
“…Culture in specific culture medium, another technique available for parasitological diagnosis, is not routinely used, given the maintenance requirements and necessary growth periods, which can be to 30 days [27] .The lower sensitivity of culture-based methods has restricted its use, however, while fostering research into alternatives that offer improved performance [28] . Noted that bone marrow aspirate culture is not the most suitable technique for VL diagnosis, considering the time constraints it places on treatment initiation [29] .…”
Section: Discussionmentioning
confidence: 99%